Performance and Project Assessment in Science Learning - I Wayan Widiana (Jurnal Pendidikan dan Pengajaran, 2022)
There are still many teachers who are less precise in carrying out assessments in learning. The purpose of this research is to develop a performance assessment and project assessment in science learning. This type of research is research development, using the ADDIE development model. The subject test consists of content test experts, design experts, expert judgments, and field tests obtained using a questionnaire/questionnaire. The data obtained were analyzed by qualitative descriptive, quantitative, and inferential statistical analysis. The result of this research is that the quality of project performance appraisal by review experts in performance appraisal is a very good qualification, namely 90.00%. The results of the subject expert test are 96.00%. Instructional test design experts in very good qualifications, namely 92.00%, while for project assessment, the qualifications are very good, namely 92%. Experts in the assessment of learning tests with very good qualifications are 90.00%, project assessments with very good qualifications are 94%, and field trials with very good qualifications are 90.76%. 91.7% for project appraisal. The effectiveness of the development of the performance appraisal obtained shows the significance is t = 4.612 > table = 2,000, while for the assessment of the results of the development of the project effectiveness assessment obtained, the significance is t = 6.93 > table = 2,000. It is concluded that there is a significant difference in student learning outcomes before and after using performance and project assessments in science learning.